When should firms share credit with employees? Evidence from anonymously managed mutual funds - Massa, Massimo; Reuter, Jonathan; Zitzewitz, Eric (Journal of Financial Economics, 2010)
We study the choice between named and anonymous mutual fund managers. We argue that fund families weigh the benefits of naming managers against the cost associated with their increased future bargaining power. Named managers receive more media mentions, have greater inflows, and suffer less return diversion due to within family cross-subsidization, but departures of named managers reduce net flows. Naming managers became less common between 1993 and 2004. This was especially true in the asset classes and cities most affected by the hedge fund boom, which increased outside opportunities for, and the cost of retaining, successful named managers.